Land Use Scanner: the continuous cycle of application, evaluation and amelioration in landuse modelling - Judith Borsboom; Wim de Regt; Kees Schotten (European Regional Science Association (ERSA), 2002)
The Land Use Scanner is a logit model that simulates future land use in a GIS environment. The model uses claims from sectoral models as input, next to physical suitability, distance decay and policy maps. The model has been applied in several planning and decision making processes, such the Fifth Nota on Physical Planning and Nature Outlook. Evaluation of these applications has led to a series of suggestions for further improvement, such as adaption of the suitability maps, fine-tuning of the translation of sectoral claims to land use claims, and refinement of the priority of allocation for different types of land use. This paper discusses briefly the development of the Land Use Scanner, its application, and the current and prospective adaptions of the model and its input.
Keywords: 330